2020
DOI: 10.7717/peerj.9759
|View full text |Cite
|
Sign up to set email alerts
|

Changes in muscle activity during the flexion and extension phases of arm cycling as an effect of power output are muscle-specific

Abstract: Arm cycling is commonly used in rehabilitation settings for individuals with motor impairments in an attempt to facilitate neural plasticity, potentially leading to enhanced motor function in the affected limb(s). Studies examining the neural control of arm cycling, however, typically cycle using a set cadence and power output. Given the importance of motor output intensity, typically represented by the amplitude of electromyographic (EMG) activity, on neural excitability, surprisingly little is known about ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 41 publications
(69 reference statements)
0
12
0
Order By: Relevance
“…The assumption made when the bEMG between tasks is similar is that the effort level to produce those tasks is also similar. In our experience and inline with leg cycling work (108), the EMG produced during arm cycling at a relatively high workload, such as 35% of maximal power output (48), is often greater than can be produced by the same muscle during a submaximal tonic contraction. In other words, the effort required to generate equivalent EMG during an isometric contraction as that produced during a submaximal bout of arm cycling may be substantially higher.…”
Section: How To Make Task Comparisons Based On Surface Emgmentioning
confidence: 90%
See 3 more Smart Citations
“…The assumption made when the bEMG between tasks is similar is that the effort level to produce those tasks is also similar. In our experience and inline with leg cycling work (108), the EMG produced during arm cycling at a relatively high workload, such as 35% of maximal power output (48), is often greater than can be produced by the same muscle during a submaximal tonic contraction. In other words, the effort required to generate equivalent EMG during an isometric contraction as that produced during a submaximal bout of arm cycling may be substantially higher.…”
Section: How To Make Task Comparisons Based On Surface Emgmentioning
confidence: 90%
“…One of the main factors for consideration when setting stimulation parameters during locomotor outputs is the phase-dependent changes in corticospinal excitability. During locomotor outputs, corticospinal excitability is largely modulated in a phase-dependent manner that closely parallels the phasic modulation of the EMG (25,31,48,55,(84)(85)(86)(87). In other words, when muscle activity is high during specific phases of the movement, the threshold to elicit evoked responses is generally low and the amplitude of these responses is typically large.…”
Section: Factors To Consider For Setting Stimulation Intensities During Rhythmic Motor Outputmentioning
confidence: 98%
See 2 more Smart Citations
“…Given a cadence, an increase in crank resistance is known to require an increased muscle activation. Arm muscle activities during arm cycling at different workloads were characterized in ( Chaytor et al, 2020 ) and it was found that there was a linear relationship between EMG amplitude and power output for individual muscles. On the other hand, an increase in muscle activation also produces an increased signal dependent motor noise.…”
Section: Introductionmentioning
confidence: 99%